Immune privilege or privileged immunity? - Forrester, J; Xu, H; Lambe, T; Cornall, R (2008)
Immune privilege is a concept that has come of age. Where previously it was considered to be a passive phenomenon restricted to certain specialized tissues, it is now viewed as comprising several mechanisms, both active and passive, shared in many aspects with emerging notions of the mechanisms of peripheral tolerance. The relative degrees of immune privilege vary from tissue to tissue depending on the number and strength of each of the mechanisms contained in that tissue. Immune privilege can be generated in non-privileged sites such as the skin and allografts, and is a property of the tissue itself. We therefore propose that, in addition to canonical central and peripheral tolerance mechanisms, there is a third route whereby the organism promotes self-antigen non-reactivity centered on the specific properties of each tissue and varying accordingly (relative degrees of immune privilege). This third mechanism of inducing immunological tolerance, as it is a local tissue phenomenon, might have particular therapeutic significance, for instance in devising strategies for induction of immunity to tumors by disrupting immune privilege or in preventing graft rejection by promoting immune privilege.